PENGARUH PELATIHAN DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. METISKA FARMA - Freddrick Tiagita Putra (Jurnal Manajemen Bisnis Krisnadwipayana, 2018)
An effective training program can improve the performance, skills, attitudes and spirit of the organization (Gomez, et al, 2001). The implementation of training and development programs must have various benefits for greater career development for future responsibilities. The purpose of this study is to analyze simultaneously and partially learning and training on the performance of employees of PT. Metiska Farma, causing 84 research respondents. The research sampling technique uses saturated samples, which is all the amount of information used as research samples. Research analysis uses simple analysis and multiple regression with hypothesis testing using t test and f test. The results showed that there were both simultaneous and partial training and leadership on the performance of employees of PT. Metiska Farma.